Design of Intelligent System for Visually Impaired to Access the Required Location - Abdeen Abdalsabour, Yosra; Mohammed Abdulwahab, Mortada (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2020)
The percentage of blinds according to the world health organization is 0.4% of the population in industrialized countries and it rises to 1% in the developing countries.This paper aimed to help these categories of people to overcome their problems to move towards any location independently. The design in this paper specified three paths in the University of Gezira to help the visually impaired students to reach different places in the university campus easily. These paths were monitored and controlled using GPS and raspberry pi technology. Three switches were used to help the blind to select his path. An important feature was provided by this system, in which when the blind gets out of the selected path, the system automatically determined how far he is away from the path and a voice massage alerted him and guided him through headphone to return in the path. Ultrasonic sensors are used to alert for any detected obstacle along the path. Moreover, the system automatically calculated the distance between the blind and obstacle, which allows the blind to avoid it easily. This system informs the blind the distance that remains to reach to the required destination. The design has been experimentally tested and the results showed that the guiding system works correctly, which proved the ability to generalize this system in other places.